Bibliometric analysis: Trends of gamification in physics learning from 2019 to 2023 - Surya Haryandi; Rossy Arlinda; Misbah Misbah; Muhdi Harto; Nurlaela Muhammad; Sunardi Sunardi (Momentum: Physics Education Journal, 2024)
This research aims to analyze research trends related to the topic of Gamification from 2019 to 2023* through bibliometric analysis using the Scopus database. Based on the criteria, 56 articles were obtained from 326 documents. These articles have been translated from international journals indexed by Scopus. The selection references were then managed using reference management software, namely Mendeley. After working on the database, this research classifies and visualizes it using VOSviewer software. The results indicate that Gamification research is gradually increasing every year. The United States, China and Japan contribute the most research globally. Visualizing gamification research trends for 2019-2023* reveal six clusters. The results of this research can support researchers regarding Gamification research trends worldwide and provide direction for further research. Overall, these reflections provide an excellent reference point for further research on Gamification.